Lysine Supply Is a Critical Factor in Achieving Sustainable Global Protein Economy - Leinonen, Ilkka; Iannetta, Pietro P. M.; Rees, Robert M.; Russell, Wendy; Watson, Christine; Barnes, Andrew P. (Frontiers in Sustainable Food Systems, 2019)
Production of animal-based protein is a significant global source of greenhouse gases, a major driver of agricultural land use and a source of nutrient loss to the environment. In this study, we provide a new assessment of the current sources of proteins in the human diet and analyze the options for increasing the use of plant-based sources, taking the protein quality, as indicated by the amino acid composition, into account. The results demonstrate the importance of sustainable global supply of lysine, one of the amino acids essential for human nutrition. It is demonstrated here that the current production of plant-based lysine that can be considered as replacement of lysine obtained from animal protein largely comes from soybean originating from a small number of countries. There are limited large-scale options to broaden the supply of plant-based lysine, namely increase of soya production outside its current main production areas, increase of production of legumes other than soya or other lysine-rich crops, obtaining plant-based lysine from sources not currently used for human consumption, or manufacturing lysine from non-standard plant-based sources (e.g., through fermentation from sugar). All of these options would require major changes in the structure of global agricultural production and associated agri-food systems and would especially have consequences on agricultural land use.